Sharing knowledge through an intervention project in a family health strategy: interfaces of the supervised nursing stage (Research, Society and Development, 2018)
This article will share an experience report resulting from the realization of an Intervention Project elaborated during the discipline of Management of Nursing Assistance in the Basic Health Network developed in a Family Health Strategy of a municipality in the interior of RS. Initially, some situations-problems that stood out in the context of the unit, after some reflections were performed, aimed to re-evaluate the flow of collection of bronchial secretion (sputum) in patients with suspected pulmonary tuberculosis biliary in the FHT. With the accomplishment of a bibliographical research linked to the intervention proposal, it was realized that the complexity of the tuberculosis situation requires a shared approach by several health professionals and the decentralization of care with strengthening of the involvement of basic attention. need of the professionals to be able to attend to this population stratum contributing to the integrality and humanization in the assistance, as well as the satisfaction of the user.